Building Civilization in the Era of Globalization Based on Knowledge Through Education and Dakwah - Muhammad Hamka; Agusman Agusman; Muh Arbiyansyah Nur (Sekolah Tinggi Agama Islam Taruna Surabaya, 2024)
In the era of globalization, characterized by global economic, technological, and cultural integration, the development of civilization has become increasingly complex. Amidst these dynamics, education and propagation of faith (dakwah) play a crucial role in shaping the foundation of a sustainable civilization. History bears witness that the presence of knowledge through education and dakwah serves as a benchmark for the rise and fall of nations. Knowledge is the light for humanity, enlightening their minds, fostering civilization, and bringing happiness. However, knowledge does not come automatically. It must be sought, learned, practiced, internalized, propagated, and held accountable to its true essence. This forms the basis for building civilization by making knowledge the foremost component. This research aims to explore the roles of education and dakwah as the foundation for civilization-building in the era of globalization, while also highlighting the challenges and opportunities in this process. The research methodology employed is qualitative analysis involving literature review and case studies. The findings indicate that education provides the knowledge and skills necessary to confront global challenges, while dakwah provides spiritual and moral guidance that forms the basis of civilizational values. Nonetheless, there are challenges in preserving religious identity and traditional values amidst the influence of foreign cultures and modern technology.